2008
DOI: 10.1666/0094-8373(2008)034[0282:siieem]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes in early Eocene mammals as indicators of forest canopy structure and resource partitioning

Abstract: The three dimensional structure of vegetation is an important component of ecosystems, yet it is difficult to reconstruct from the fossil record. Forests or woodlands prevailed at mid-latitudes in North America during the early Eocene but tree spacing and canopy structure are uncertain. Here we use stable carbon isotope values (␦ 13 C ) in early Eocene mammalian faunas to infer canopy structure. We compare ␦ 13 C values in two diverse fossil assemblages from the central Bighorn Basin to values predicted for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 80 publications
(119 reference statements)
3
49
0
1
Order By: Relevance
“…In the latter case, only a few taxa were analyzed, probably compromising estimates of average compositions. Several other paleoenvironments were viewed as particularly wet, either from paleobotanical and paleofaunal observations or because of geographic location (20,21,25,26). For three of these studies, estimates of average MAP for these localities exceed 2;000 mm∕yr.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, only a few taxa were analyzed, probably compromising estimates of average compositions. Several other paleoenvironments were viewed as particularly wet, either from paleobotanical and paleofaunal observations or because of geographic location (20,21,25,26). For three of these studies, estimates of average MAP for these localities exceed 2;000 mm∕yr.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, clades that correspond to all other extant genera diverged in the Early to Mid-Eocene (ca 49-40 Myr ago), and these contain primarily arboreal species (figure 2). The latter could point to an adaptive radiation, owing to increased ecological opportunity [61], associated with expansion of forest environments in Africa and Madagascar connected to Greenhouse Earth conditions during the Early Eocene Climatic Optimum ca 51-53 Myr ago [62][63][64][65][66][67]. Post-Palaeocene Madagascar left a subtropical arid belt as it drifted northward towards the equator, which led to a significant increase in moisture levels on the island.…”
Section: Discussionmentioning
confidence: 99%
“…δ 13 C E in mammalian herbivores reflects the δ 13 C value of the vegetation they consume, with predictable enrichment (19). Plants in turn track the δ 13 C value of atmospheric CO 2 , with influences from environmental factors such as humidity and vegetation density (20,21). At Cabin Fork, phenacodontids (Ectocion and Copecion) record a negative shift of ~4.6 per mil (‰) in δ 13 C E at the onset of the CIE (Figure 2A).…”
mentioning
confidence: 99%
“…Coryphodon was a large water-dependent or semi-aquatic mammal (21,23). Studies of ecologically similar living mammals have shown that their δ 18 O E faithfully records the δ 18 O of surface water (24,25), which in turn is strongly correlated with air temperature at mid-to high latitudes (26).…”
mentioning
confidence: 99%